Miejsca zapisane i przemilczane w poezji Ireny Dowgielewicz = Outspoken and silent places in Irena Dowgielewicz's poetry - Szott, Mirosława (1987- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Irena Dowgielewicz (born in 1917 in Kyev) belongs to the oldest generation of Lubusz poets. Her literary work is looked upon from different perspectives, as it contains both female and sacral themes. In my article, I attempt to focus on her portraying places. I am interested in topography, which the author of "The Poplar Landscape" understands literally, but also as reversing the place (Eastern borderlands, Warsaw) and referring to its hidden meaning ("So we keep quiet bearing old cities"). Another aspect I touch upon in the present article is the affective level of topography, which I see as the expression of emotions toward a place.
Keywords: literacka topografia; miejsce; afekt; poezja lubuska; Gorzów Wielkopolski (woj. lubuskie); Dowgielewicz, Irena (1917-1987); literary topography; place; affect; Lubusz poetry